Research on Android security of broadcasting mechanism - Sihan QING (Dianxin kexue)
In recent years, there has been increased interest in the research of Android component security. Broadcast receiver is one of the 4 components in Android, strangely enough, few papers have been published regarding to its security. Android broadcasting mechanism, and its security framework and features based on this were analyzed. According to the security challenges of Android broadcasting mechanism, the corresponding countermeasures and solutions were proposed. Finally, a summary of the results and the future research directions were given.